Dentistry and Intensive Care Unit: A Brief Report - Bannwart, Lisiane Cristina; de Moraes Melo Neto, Clóvis Lamartine; dos Santos, Daniela Micheline; Moreno, André Luiz de Melo; Pesqueira, Aldiéris Alves; Goiato, Marcelo Coelho; de Magalhães Bertoz, André Pinheiro (European Journal of Dentistry, 2021)
Objective The aim of this study is to verify whether removable dentures of patients admitted to an intensive care unit (ICU) are niches of microorganisms that can cause pathologies (Staphylococcus aureus, Candida spp., and enterobacteria).Materials and Methods Fifteen patients who were denture wearers (removable partial denture and complete denture) were included in this study. Patients must wear their dentures daily, and these dentures must have acrylic parts. Microbial biofilm was collected from the acrylic part of one denture of each patient. Then, the biofilm was seeded on different culture media: Sabouraud agar, blood agar, MacConkey agar, and mannitol salt agar. In this study, biochemical evaluations of microorganisms were performed.Statistical analysis The percentage of dentures with the microorganism identified by each culture medium was calculated.Results In total, 100% of the dentures were positive for Staphylococcus spp. (blood agar) and Candida spp. (Sabouraud agar); 33.3% of the dentures were positive for S. aureus (Mannitol salt agar); and 13.3% of the dentures were positive for Shigella spp. (MacConkey agar).Conclusion Removable dentures of patients (removable partial dentures and complete dentures) admitted to an ICU are niches of microorganisms that can cause pathologies.
Keywords: complete denture; intensive care units; removable partial denture; dental prosthesis; cross infection; acrylic resin